The study of clinical profile and assess the outcome of preterm infants diagnosed to have clinically significant PDA - Mallick, Bhabagrahi; Nayak, Sarthak R.; Tripathy, Subrat Ku. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Patency of ductus arteriosus is vital for fetal survival. Ductus often fails to close in premature infants called patent ductus arteriosus (PDA). Our objective is to find the clinical profile and assess the outcome of preterm infants diagnosed to have clinically significant PDA. Methods: 20 infants diagnosed as PDA clinically and confirmed by echocardiography. Symptomatic infants initially treated with fluid restriction and frusemide. Non responders treated with per rectal ibuprofen with dose of 10 mg/kg stat followed by 5 mg/kg x 2 doses at 24 hour intervals. Failure to ductal closure followed by similar second course of ibuprofen. Echocardiography repeated after 72 hours of each therapy. Surgical ligation of ductus was carried after failure to drug therapies. Secondary outcomes during hospitalization were documented. Results: PDA was diagnosed in seventeen infants during first week and three after seven postnatal day. Mean gestational age and birth weight were 31±2 weeks and 1466±378grams respectively. Three babies responded well to fluid therapy. Thirteen infants out of seventeen had ductal closure after first course and two to second course of ibuprofen. Two had undergone surgical treatment. Six infants detected with sepsis, five with intraventricular hemorrhage and retinopathy of prematurity. Two developed bronchopulmonary dysplasia. Pulmonary hemorrhage and NEC were found in one each. Two babies died. Conclusions: PDA is inversely related to gestational age and birth weight. Prostaglandin synthase inhibitors are essential in ductal closure. Surgical ligation is reserved for medical therapy failure. Co-morbidities in PDA are less in well treated babies.